Long-term safety and efficacy of weekly subcutaneous tocilizumab monotherapy in patients with rheumatoid arthritis who had an inadequate response to subcutaneous tocilizumab every other week: Results from the open-label extension of the SHINOBI study. Issue 5 (3rd September 2019) - Ogata, Atsushi; Tanaka, Yoshiya; Ishii, Tomonori; Kaneko, Motohide; Miwa, Hiroko; Ohsawa, Shino; Yamakawa, Reiji; ,
Abstract: Objective: To evaluate the long-term safety and efficacy of subcutaneous tocilizumab (TCZ-SC) monotherapy administered weekly (qw) in patients with rheumatoid arthritis who had an inadequate response to TCZ-SC every other week (q2w). Methods: Patients who completed 12 weeks of double-blind treatment with either TCZ-SC q2w monotherapy or TCZ-SC qw monotherapy were switched to or continued to receive open-label treatment with TCZ-SC qw monotherapy for 40 weeks. Safety and efficacy were assessed. Subgroup analyses of Disease Activity Score based on 28 joints using erythrocyte sedimentation rate (DAS28-ESR) were performed at 12 weeks. Results: The incidence of adverse events was 464.4/100 patient-years (PY). The incidence of infection was 121.3/100 PY. The safety profile of TCZ-SC qw monotherapy was consistent with that of prior studies of TCZ. No additional safety concerns were observed. Improvement from baseline in DAS28-ESR was maintained at week 52 in patients who continued TCZ-SC qw and improved in patients who switched from TCZ-SC q2w to qw. At week 12, the efficacy of TCZ-SC qw monotherapy was greater than that of TCZ-SC q2w monotherapy irrespective of weight and BMI subgroups. Conclusion: The long-term weekly dosing of TCZ-SC monotherapy was well tolerated and efficacy was maintained over 52 weeks.